Integrated analysis of lncRNA and mRNA expression profiles in cutaneous leishmaniasis lesions caused by Leishmania tropica - Hadifar, Shima; Masoudzadeh, Nasrin; Andersson, Björn; Heydari, Hossein; Mashayekhi Goyonlo, Vahid; Kerachian, Mohammadali; Persson, Josefine; Rahimi-Tamandegani, Hasan; Erfanian Salim, Reza; Rafati, Sima; Harandi, Ali M. (Frontiers in Cellular and Infection Microbiology, 2024)
BackgroundCutaneous leishmaniasis (CL), caused by Leishmania (L.) species, remains a neglected tropical disease in many developing countries. We and others have shown that different Leishmania species can alter the gene expression profile of human host cells. Long non-coding RNAs (lncRNAs) have been found to play a role in the pathogenesis of leishmaniasis through dysregulation of transcriptome signatures. Understanding the regulatory roles of lncRNAs in the biological networks involved in leishmaniasis can improve our understanding of the disease.MethodsHerein, we used our previous RNA sequencing data (GSE216638) to investigate the profile of lncRNAs in the skin lesions of L. tropica-infected patients. We employed the weighted gene correlation network analysis (WGCNA) algorithm to establish co-expression networks of shared genes between CL patients and infer the potential role of lncRNAs in CL patients. We identified hub genes and trans- and cis-acting lncRNAs, and carried out functional enrichment analysis on a key co-expressed module related to L. tropica-infected patients.ResultsWe found substantial involvement of lncRNAs in the CL patient dataset. Using the WGCNA method, we classified all included genes into seven modules, with a module (turquoise) being significantly correlated with the studied clinical traits and identified as the key module. This module was mainly involved in the “interferon gamma signaling” and “cytokine signaling” pathways. We highlighted several lncRNAs and their co-expressed mRNA pairs, like SIRPG-AS1, IL21R-AS1, IL24, and TLDC2, as hub genes of the key module. Quantitative RT-PCR validated the expression of several genes in the lesions of an independent cohort of L. tropica-infected patients.ConclusionsThese findings enhance our understanding of the human skin response to L. tropica infection. Furthermore, the hub genes identified in this study are worthy of further evaluation as potential targets in the development of more effective treatments and preventive measures for CL caused by L. tropica.